Opportunities for the Use of Artificial Intelligence in Literature Teaching - Surmanidze, Tamar (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2026)
The aim of the article is to present the role, possibilities, and challenges of artificial intelligence. The subject of analysis is the role of AI in text analysis, modeling of character relationships, stimulating creative writing, and supporting individual learning.The article discusses the role of artificial intelligence in the modern educational system, specifically in the process of teaching literature. It describes how AI tools help teachers make the learning process more engaging and effective for students. Research findings are provided to show how appropriately students and teachers use artificial intelligence.The analysis of the research results confirms that the integration of artificial intelligence in literature teaching creates innovative opportunities. AI facilitates in-depth text analysis, understanding of character relationships, and the development of students’ creative skills. However, its effectiveness depends on the methodical approaches chosen by the teacher. To improve the quality of humanities education, it is essential to synthesize traditional teaching methods with innovative technologies.